2015
DOI: 10.3390/e17052677
|View full text |Cite
|
Sign up to set email alerts
|

Projective Synchronization of Chaotic Discrete Dynamical Systems via Linear State Error Feedback Control

Abstract: A projective synchronization scheme for a kind of n-dimensional discrete dynamical system is proposed by means of a linear feedback control technique. The scheme consists of master and slave discrete dynamical systems coupled by linear state error variables. A kind of novel 3-D chaotic discrete system is constructed, to which the test for chaos is applied. By using the stability principles of an upper or lower triangular matrix, two controllers for achieving projective synchronization are designed and illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Xu [21] showed that the scaling factor of PS in coupled partially linear systems is unpredictable and can be arbitrarily maneuvered by introducing a feedback control to master systems. The PS between two chaotic discrete dynamical systems was achieved by Xin and Wu [22] via linear state error feedback control. Wen and Xu [23] and Yan and Li [24] extended the projective synchronization feature to general nonlinear systems, including non-partially linear chaotic systems, by applying controllers to response systems, which is called generalized projective synchronization (GPS) and was studied later [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Xu [21] showed that the scaling factor of PS in coupled partially linear systems is unpredictable and can be arbitrarily maneuvered by introducing a feedback control to master systems. The PS between two chaotic discrete dynamical systems was achieved by Xin and Wu [22] via linear state error feedback control. Wen and Xu [23] and Yan and Li [24] extended the projective synchronization feature to general nonlinear systems, including non-partially linear chaotic systems, by applying controllers to response systems, which is called generalized projective synchronization (GPS) and was studied later [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…We can formulate the 0-1 test algorithm [16][17][18][19][20][21] as follows. Suppose φ(n) is a discrete set of measurement data sampled at times n = 1, 2, 3, · · · , N, where N is the total amount of the data.…”
Section: -1 Test Algorithm For Chaosmentioning
confidence: 99%
“…At present, there are an increasing number of control theories, and parts of them even have been applied in practice for many years such as PID control [8,9], adaptive control [10][11][12][13], and feedback control [14][15][16] and so on. On the contrary, many remarkable state-of-the-art control methods, which enjoy a variety of advantages compared to traditional control methods, are being developed.…”
Section: Introductionmentioning
confidence: 99%